2017
DOI: 10.1108/jsm-08-2016-0289
|View full text |Cite
|
Sign up to set email alerts
|

Bricks or clicks? Understanding consumer usage of retail mobile apps

Abstract: Purpose Mobile apps represent an emergent self-service technology that has greatly contributed to the rise of mobile shopping. However, the existing services and marketing literature offer little insight on consumer app usage. Further, little is known about how this app usage might affect important outcomes such as consumers’ intentions to use and recommend an app, their channel preferences (in-store vs app), or their purchasing behavior with the app. Thus, the purpose of this research is to examine if, and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
83
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(103 citation statements)
references
References 45 publications
4
83
0
9
Order By: Relevance
“…Moreover, the feedback of past behavior (see, Anesbury, Talbot, Day, Bogomolov, & Bogomolova, 2020;Sharp et al, 2012) should be taken into account, as it is likely to underpin continued use, irrespective of it resulting from a more thoughtful evaluation of the app's benefits or simpler decision-making based on recognizing the branded app. On occasion, past research on mobile apps has considered the feedback of past behavior primarily in relation to the initial adoption of apps (e.g., Kim, Kim, Choi, & Trivedi, 2017;Liu, Zhao, & Li, 2017;Newman, Wachter, & White, 2018;Viswanathan et al, 2017). Therefore, there is scope for considering the role of past behavior in the decisionmaking process leading to the continued use of branded apps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the feedback of past behavior (see, Anesbury, Talbot, Day, Bogomolov, & Bogomolova, 2020;Sharp et al, 2012) should be taken into account, as it is likely to underpin continued use, irrespective of it resulting from a more thoughtful evaluation of the app's benefits or simpler decision-making based on recognizing the branded app. On occasion, past research on mobile apps has considered the feedback of past behavior primarily in relation to the initial adoption of apps (e.g., Kim, Kim, Choi, & Trivedi, 2017;Liu, Zhao, & Li, 2017;Newman, Wachter, & White, 2018;Viswanathan et al, 2017). Therefore, there is scope for considering the role of past behavior in the decisionmaking process leading to the continued use of branded apps.…”
Section: Introductionmentioning
confidence: 99%
“…In the specific instance of mobile apps, past research has seldom considered the influence of past behavior and, when accounting for it, it has been considered primarily as a determinant of apps' adoption and initial use. For example, a few studies have highlighted as important drivers of apps' discovery and use: (a) mobile experience and browsing behavior (e.g., Kim et al, 2017); (b) acquisition frequency and recency (Liu et al, 2017); (c) usage frequency and recency (Newman et al, 2018;Viswanathan et al, 2017); and (d) active app usage or consumer voluntary participation (Chung, 2015;Mäki & Kokko, 2017). Moreover, empirical studies based on the analysis of panel data revealed that many categories of apps are characterized by high levels of usage concentration.…”
mentioning
confidence: 99%
“…Kang and Namkung [15] in their study on food delivery mobile apps investigated the impact of personalization on continuance intention through several mediating factors. Personalizing app usage experiences, conceptualized as "self-app connection", where a user incorporates apps into their self-concept, influences the actual as well as future purchase intentions [24].…”
Section: Personalization and Continuous Use Intentionmentioning
confidence: 99%
“…In addition to this, most studies related to the intersection of users and technology, and particularly to those concerning apps, have largely focused on intention and initial adoption [23,24], while at the same time, the UTAUT2 model has not been fully explored to address the issue of continuous intention.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some studies have focused on mobile apps' value-in-use in various usage contexts (e.g., Fang 2019;Bruns and Jacob 2014). Additionally, evidence has been found that previous user experiences have a moderating effect on the evaluation and use of mobile K apps (e.g., Hart and Sutcliffe 2019;Newman et al 2018;Workman 2014). To our knowledge, studies concerning the effects of user experience on value-in-use and their temporally dynamic nature in the context of LBS have not been conducted, and no studies have examined the impact of shopping patterns on value-in-use in this context.…”
Section: Introductionmentioning
confidence: 99%